Perspektif mahasiswa farmasi universitas mataram terhadap vaksinasi COVID-19 - Nur Amalina Sabdarrifa; Baiq Bismiranti Haris; Zulfiana Fitrianingrum Annas; Candra Eka Puspitasari (Universitas Mataram, 2022)
COVID-19 is an infectious disease caused by SARS-CoV-2 with a high transmission rate. The Indonesian Ministry of Health made efforts to contain the spread of the virus by conducting a vaccination program. This study’s objective to examine the extent to which UNRAM Pharmacy students provide the opportunity to vaccinate, the known types of COVID-19 vaccines, and student responses to the outbreak of the emergence of a new variant, namely the COVID-19 Delta variant. The method used in this study was cross-sectional, with a sample of 163 active students of Pharmacy UNRAM. Sampling was done boldly by using google forms. The results of the study were 98% of respondents started to vaccinating against COVID-19. There are three types of vaccines known to students, namely Sinovac, Astra Zeneca, and Moderna.